2011
DOI: 10.1590/s0103-50532011000700021
|View full text |Cite
|
Sign up to set email alerts
|

Prenylindole alkaloids from Raputia praetermissa (Rutaceae) and their chemosystematic significance

Abstract: O extrato diclorometano do caule de Raputia praetermissa levou ao isolamento de quatro compostos novos, 4-desóxi-raputindol C (1), raputimonoindol A-B (2, 3) e hexadecanil 2-hidróxi-4-metóxi-cinnamato (5), juntamente com os alcalóides 5-(4-metóxi-metilfuran-2-il)-1H-indol (raputimonoindol C), furoquinolinos maculosidine, robustine, evolitrine e dictamnine. O estudo do extrato hexano levou ao isolamento de N-metil-4-metóxi-quinolin-2(1H)-ona, skimmianina, cicloartenona, sitosterol, stigmasterol e sitostenona. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Now, the ethyl allyl ether side product could be removed by flash chromatography on RP‐18 silica gel. The optical rotatory power of ent ‐raputimonoindole A ( ent ‐ 3 , [ α ] D 20 = +38.7, c = 0.52, MeOH) was found to be opposite to that of the natural product 3 ([ α ] D 25 = –41, c = 0.003, CHCl 3 ) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Now, the ethyl allyl ether side product could be removed by flash chromatography on RP‐18 silica gel. The optical rotatory power of ent ‐raputimonoindole A ( ent ‐ 3 , [ α ] D 20 = +38.7, c = 0.52, MeOH) was found to be opposite to that of the natural product 3 ([ α ] D 25 = –41, c = 0.003, CHCl 3 ) …”
Section: Resultsmentioning
confidence: 99%
“…The biosynthesis of the raputindoles probably involves oxidative homo and heterodimerization of 5‐, 6‐, and 7‐prenylindole, as supported by the occurrence of 5‐ and 7‐prenylindole in the same species . The 5‐prenyl side chain can also be oxygenated and cyclized to form furan systems, as in the raputimonoindoles A–C and congeners from R. simulans and R. praetermissa , . Raputimonoindole A ( 3 ) exhibits an additional prenyl side chain installed at the furan‐derived moiety.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition different furoquinoline alkaloids have also been isolated from other members of the Rutaceae family. Thus, Rosas et al, 2011 [ 25 ], reported the presence of the furoquinolines maculosidine, robustine, and evolitrine among others, from the Raputia praetermissa species. Also, from the Zanthoxylum buesgenii species, three known furoquinolines have been reported: maculine, kokusaginine, and teclearverdoornine [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“… 1 Deoxiraputindole C ( 5 ) is another member of this family, which was isolated in 2011 from Raputia praetermissa , collected in the Brazilian Amazon forest. 2 Structurally, this is a rare new class of indole alkaloid as it features unsubstituted N-1, C-2, and C-3 positions. 1 Other natural products containing the 1,2,3-unsubstituted pattern are trikentrin A 3 and the alkaloids from the herbindole family.…”
mentioning
confidence: 99%